ACUTE RADIATION TOXICITY IN PATIENTS WITH GLIOBLASTOMA TREATED WITH HYPOFRACTIONATED RADIOTHERAPY: Acute Toxicity of Hypofractionated Radiotherapy in Glioblastoma - Stepanović, Aleksandar; Arsenijević, Tatjana; Tomašević, Aleksandar; Bogdanović, Ivan; Kopčalić, Katarina; Poparić-Banđur, Bojana; Nikitović, Marina (Medical Research, 2024)
Introduction. Hypofractionated radiotherapy is the preferred regimen for older patients with glioblastoma and those with poor prognostic factors. Acute radiation toxicity remains a concern in these cases. Aim. We conducted a retrospective analysis aiming to show the acute toxicity profile in patients with glioblastoma treated with hypofractionated radiotherapy, with or without temozolomide. Material and Methods. This study included 25 patients with diagnosed glioblastoma who underwent a hypofractionated regimen of radiotherapy, with a dose of 40 Gy in 15 fractions or 34 Gy in 10 fractions. Acute radiation toxicity was observed during the treatment and graded according to Common Terminology Criteria for Adverse Events, version 5.0. Results. Radiation toxicity was experienced in 60% of the patients. The majority of the patients with toxicity (80%) had toxicity grade 1. One patient (6.7%) exhibited grade 3 radiation toxicity. No patients had grade 4 radiation toxicity. A statistically significantly higher number of patients who experienced radiotoxicity were predominantly distributed in the group with tumors located in more than 1 lobe, multifocal or multicentric tumor compared to patients who had a tumor in one lobe (p < 0.01). Conclusions. A hypofractionated regimen of radiotherapy represents a favorable option for the treatment of older patients with glioblastoma or those with poor prognosis, with an acceptable acute radiation toxicity profile.